Development of Learning Modules Based on a Realistic Mathematical Approach with Autograph Software to Improve Creative Mathematical Thinking Ability Students of SMP Negeri 1 Blangkejeren - Rike Ahmadi; Edi Syahputra; Bornok Sinaga (BIRCU, 2021)
This study aims to analyze the practicality of the learning modules developed based on the Realistic Mathematical Approach with autograph software, to analyze the effectiveness of the learning modules developed based on the Realistic Mathematical Approach assisted by autograph software, and to describe the improvement of students' mathematical creative thinking abilities through learning modules developed based on the Mathematical Approach. Realistic assisted autograph software. The data were obtained through the learning module validity sheet consisting of the lesson plan validation sheet and the mathematical creative ab ility test validation sheet, student response questionnaires and teacher interview guidelines for the learning module and the learning module effectiveness instrument seen from the students' mathematical creative test results. Module development in this study uses the Thiagarajan, Semmel and Semmel development models, namely the 4-D model (define, design, develop, disseminate). The results of the research were students and teachers stated that the developed device was easy to use, the students' critical thinking ability obtained classical completeness with a percentage of 87.5%, the level of student activity met the ideal time tolerance criteria set, student responses to the components of learning devices and learning activities is positive. The increase in creative thinking skills in the first try was 77.9, an increase in the second try to 81.64.